2015
DOI: 10.3344/kjp.2015.28.3.198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Intraoperative Esmolol on Pain Management Following Lower Limb Orthopedic Surgery

Abstract: BackgroundLack of proper control of acute postoperative pain often leads to lingering or chronic pain. Several studies have emphasized the role of beta-blockers in reducing postoperative pain. Esmolol is a selective short-acting beta-blocker that produces few side effects. The purpose of this study was to examine the effect of intravenous intraoperative esmolol on postoperative pain reduction following orthopedic leg fracture surgery.MethodsIn a clinical trial, 82 patients between 20-65 years of age with tibia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Propranolol alone ( Chen et al, 2012 ) or combined with lidocaine or dopamine ( Chen et al, 2015 ) intensified the analgesia against skin nociceptive stimuli in rats. Similar observations were reported for other β-adrenergic antagonists as atenolol ( Zaugg et al, 1999 ), labetalol ( Xiao et al, 2008 ), and esmolol ( Chia et al, 2004 ; Collard et al, 2007 ; Haghighi et al, 2015 ). In another study, β 2 -adrenergic receptors modulated both opioid tolerance and physical dependence.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Propranolol alone ( Chen et al, 2012 ) or combined with lidocaine or dopamine ( Chen et al, 2015 ) intensified the analgesia against skin nociceptive stimuli in rats. Similar observations were reported for other β-adrenergic antagonists as atenolol ( Zaugg et al, 1999 ), labetalol ( Xiao et al, 2008 ), and esmolol ( Chia et al, 2004 ; Collard et al, 2007 ; Haghighi et al, 2015 ). In another study, β 2 -adrenergic receptors modulated both opioid tolerance and physical dependence.…”
Section: Discussionsupporting
confidence: 85%
“…For example, blockade of β-adrenoceptors in the joints connecting the jawbone to the skull induced antinociception in experimental animals ( Fávaro-Moreira et al, 2012 ). In clinical studies, esmolol ( Chia et al, 2004 ; Collard et al, 2007 ; Haghighi et al, 2015 ), atenolol ( Zaugg et al, 1999 ), and labetalol ( Xiao et al, 2008 ) demonstrated analgesic properties and reduced the recurrent postoperative pain. Coloma et al (2001) suggested that perioperative β-antagonist administration was an alternative to opioids to maintain postoperative analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on TJR pain management during hospitalization [7][8][9][10][11][12] with less attention paid to addressing the management of pain after discharge. Currently, prescription pain medications such as opioids are the most common approach to managing pain postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Esmolol is often used to maintain hemodynamic stability; it also relieves stress during surgery and lowers the requirement for narcotics postoperatively. [9,10] However, the use of esmolol to alleviate agitation in children has received little research attention. Many children become agitated after strabismus surgery because the eyes are covered postoperatively, although the exact reason remains unclear.…”
Section: Introductionmentioning
confidence: 99%